Corporate social responsibility: Contribution to sustainable development and to effective management of European enterprises - Vaxevanidou, Dr. Maria (SPOUDAI Journal of Economics and Business, 2008)
The aim of this paper is to present the European Commission’s positions and propositions about Corporate Social Responsibility (CSR) and to describe a managerial model the European companies can apply, concerning the tripartite dimension (social, environmental and economic) of Corporate Social Responsibility the European Union Institutions have already determined. Till now, there is not a concrete definition for the CSR could be commonly accepted on international level. For the European Commission, CSR is essentially a concept whereby companies can decide voluntarily to contribute to a better society and a cleaner environment. In the end of this paper, it is described a managerial model can be applied according to the European vision of CSR, using the Deming’s Quality Circle (PDCA). JEL Classifications: M14, Q01